Rapid detection of SARS-CoV-2 RNA using Reverse Transcription Recombinase Polymerase Amplification (RT-RPA) with Lateral Flow for N-protein gene and variant-specific deletion-insertion mutation in S-protein gene - Malaga Granda, Jose Luis (2023)
Rapid molecular testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants may contribute to the development of public health measures, particularly in resource-limited areas. Reverse transcription recombinase polymerase amplification using a lateral flow assay (RT-RPA-LF) allows rapid RNA detection without thermal cyclers. In this study, we developed two assays to detect the SARS-CoV-2 nucleocapsid (N) gene and Omicron BA.1 spike (S) gene-specific deletion–insertion mutations (del211/ins214). Both tests had a detection limit of 10 copies/μL in vitro and the detection time was approximately 35 min from incubation to detection. The sensitivities of SARS-CoV-2 (N) RT-RPA-LF by viral load categories were 100% for clinical samples with high (> 9015.7 copies/μL, cycle quantification (Cq): < 25) and moderate (385.5–9015.7 copies/μL, Cq: 25–29.9) viral load, 83.3% for low (16.5–385.5 copies/μL, Cq: 30–34.9), and 14.3% for very low (< 16.5 copies/μL, Cq: 35–40). The sensitivities of the Omicron BA.1 (S) RT-RPA-LF were 94.9%, 78%, 23.8%, and 0%, respectively, and the specificity against non-BA.1 SARS-CoV-2-positive samples was 96%. The assays seemed more sensitive than rapid antigen detection in moderate viral load samples. Although implementation in resource-limited settings requires additional improvements, deletion–insertion mutations were successfully detected by the RT-RPA-LF technique.